(untitled) (Journal of Human Sciences, 2024)
The present paper deals with the concept of “الإيقونية ”, a translation of the term Iconicity,one of the key concepts of cognitive linguistics. Iconicity, which is generally defined as the study of the relationship between form and meaning in a linguistic unit, is conceived in this paper to encompass and address much of the issue of linguistic usage,particularly in the cases of words the forms of which are loaded with what suggests their meaning. The issue is broader than a mere imitation. The concept has been applied to examples of Arabic language uses. The research study has also investigated to what extent iconicity was present in the commentators’ interpretations of some of the Quranic verses and Quranic scripts, mainly those with unfamilar word spelling and diactric forms.The research findings have highlighted the importance of iconicity in the linguistic phenomenon and the extent of its ability to explain many linguistic uses in different contexts.